2013
DOI: 10.1002/asna.201311899
|View full text |Cite
|
Sign up to set email alerts
|

Formation of (exo–)planets

Abstract: In this small review I will address three recent topics in the field of theoretical planet formation studies. This review is not meant to be complete in any way. It is meant to give an idea where some of the recent developments are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Christophe Pinte indicated that a classical theory of planetesimal formation has shortcomings in the mechanism of collisional grain growth, which has not yet been resolved by observations (Pinte, 2015). Meter-sized dust aggregates collide so fast that they cannot stick to grow further, but they suffer from fragmentation, the so-called fragmentation barrier (e.g., Dullemond, 2013). However, Wada et al (2009) have shown that dust aggregates consisting of submicrometer-sized grains can go beyond the fragmentation barrier, if they are composed of ices.…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…Christophe Pinte indicated that a classical theory of planetesimal formation has shortcomings in the mechanism of collisional grain growth, which has not yet been resolved by observations (Pinte, 2015). Meter-sized dust aggregates collide so fast that they cannot stick to grow further, but they suffer from fragmentation, the so-called fragmentation barrier (e.g., Dullemond, 2013). However, Wada et al (2009) have shown that dust aggregates consisting of submicrometer-sized grains can go beyond the fragmentation barrier, if they are composed of ices.…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…But because dust grains migrate, this is not the case in discs. -The underlying growth model remains simple and does not consider more complex effects that have been shown to affect the evolution of the dust population in young discs (see Dullemond 2013, for a recent review): for instance, bouncing or fragmentation barrier, charging barrier or porosity evolution (Okuzumi et al 2012). -The radial gas flow, which may be important in the very central parts of the disc was not considered here.…”
Section: Model Limitationsmentioning
confidence: 99%
“…Current formation theories postulate that proto-planetary cores form in metal-rich accretion disks surrounding the host star. These proto-planets co-evolve with the disk and can undergo orbital decay due to torque asymmetries in the surrounding disk material (Armitage 2011;Mordasini et al 2012;Dullemond 2013).…”
Section: Introductionmentioning
confidence: 99%